Measuring Tumor Metabolism in Pediatric Diffuse Intrinsic Pontine Glioma Using Hyperpolarized Carbon-13 MR Metabolic Imaging. (30th July 2018) - Autry, Adam W.; Hashizume, Rintaro; James, C. David; Larson, Peder E. Z.; Vigneron, Daniel B.; Park, Ilwoo
Abstract : Objective . The purpose of this study was to demonstrate the feasibility of using hyperpolarized carbon-13 ( 13 C) metabolic imaging with [1- 13 C]-labeled pyruvate for evaluating real-time in vivo metabolism of orthotopic diffuse intrinsic pontine glioma (DIPG) xenografts. Materials and Methods . 3D 13 C magnetic resonance spectroscopic imaging (MRSI) data were acquired on a 3T scanner from 8 rats that had been implanted with human-derived DIPG cells in the brainstem and 5 healthy controls, following injection of 2.5 mL (100 mM) hyperpolarized [1- 13 C]-pyruvate. Results . Anatomical images from DIPG-bearing rats characteristically exhibited T2 -hyperintensity throughout the cerebellum and pons that was not accompanied by contrast enhancement. Evaluation of real-time in vivo 13 C spectroscopic data revealed ratios of lactate-to-pyruvate (p < 0.002 ), lactate-to-total carbon (p < 0.002 ), and normalized lactate (p < 0.002 ) that were significantly higher in T2 lesions harboring tumor relative to corresponding values of healthy normal brain. Elevated levels of lactate in lesions demonstrated a distinct metabolic profile that was associated with infiltrative, viable tumor recapitulating the histopathology of pediatric DIPG. Conclusions . Results from this study characterized pyruvate and lactate metabolism in orthotopic DIPG xenografts and suggest that hyperpolarized 13 C MRSI may serve as a noninvasive imaging technique for in vivo monitoring of biochemical processes in patients with DIPG.